2021
DOI: 10.1186/s12864-021-07864-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential association on gene-disease network via dual hypergraph regularized least squares

Abstract: Background Identifying potential associations between genes and diseases via biomedical experiments must be the time-consuming and expensive research works. The computational technologies based on machine learning models have been widely utilized to explore genetic information related to complex diseases. Importantly, the gene-disease association detection can be defined as the link prediction problem in bipartite network. However, many existing methods do not utilize multiple sources of biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Because they do not change the coded amino acids, synonymous mutations were once mistakenly thought to have no biological function ( Hong et al, 2020 ; Tang et al, 2020 ; Cheng et al, 2021a ). However, later systematic studies have shown that synonymous mutations are involved in a variety of biological processes and play important roles in the occurrence and development of diseases ( Li et al, 2020b ; Yang et al, 2021a ). Whole genome sequencing using reversible terminator chemistry can generate accurate nucleotide sequences of billions of bases at low cost ( Bentley et al, 2008 ), which greatly improves the data obtained in sequencing projects.…”
Section: Introductionmentioning
confidence: 99%
“…Because they do not change the coded amino acids, synonymous mutations were once mistakenly thought to have no biological function ( Hong et al, 2020 ; Tang et al, 2020 ; Cheng et al, 2021a ). However, later systematic studies have shown that synonymous mutations are involved in a variety of biological processes and play important roles in the occurrence and development of diseases ( Li et al, 2020b ; Yang et al, 2021a ). Whole genome sequencing using reversible terminator chemistry can generate accurate nucleotide sequences of billions of bases at low cost ( Bentley et al, 2008 ), which greatly improves the data obtained in sequencing projects.…”
Section: Introductionmentioning
confidence: 99%